1994
DOI: 10.1007/bf02416996
|View full text |Cite
|
Sign up to set email alerts
|

Noninflammatory sclerosis of the sternal end of the clavicle: a follow-up study and review of the literature

Abstract: The cases of 14 adult females with swelling, tenderness, and sclerosis of the inferomedial part of the clavicle are presented. They were seen during a 16-year period, suggesting that the condition is rare. In ten patients strain at the sternoclavicular joint seemed to be an etiological factor. Eleven patients were followed for periods of 1-13 years (mean 5 years). The clavicular sclerosis regressed and they all developed signs of osteoarthrosis. Based upon available biopsy results and review of reported cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Lesions in the manubriosternal junction were associated with a high proportion of inflammatory arthritides (70%, 7/10). Jurik et al (23) reported radiographic sclerotic changes in the sternoclavicular joint with swelling and tenderness even after longterm clinical follow-up. Histopathological findings from these lesions were non-specific, which suggests that inflammatory arthritides is difficult to confirm with percutaneous needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions in the manubriosternal junction were associated with a high proportion of inflammatory arthritides (70%, 7/10). Jurik et al (23) reported radiographic sclerotic changes in the sternoclavicular joint with swelling and tenderness even after longterm clinical follow-up. Histopathological findings from these lesions were non-specific, which suggests that inflammatory arthritides is difficult to confirm with percutaneous needle biopsy.…”
Section: Discussionmentioning
confidence: 99%